Celastrol inhibits prostaglandin E2-induced proliferation and osteogenic differentiation of fibroblasts isolated from ankylosing spondylitis hip tissues in vitro - Zou YC; Yang XW; Yuan SG; Zhang P; Li YK (Dove Medical Press, 2016)
Yu-Cong Zou,1,* Xian-Wen Yang,2,* Shi-Guo Yuan,1 Pei Zhang,1 Yi-Kai Li11School of Traditional Chinese Medicine, Southern Medical University, 2The Third Affiliated Hospital, Guangzhou University of Traditional Chinese Medicine, Guang Zhou, People’s Republic of China*These authors contributed equally to this workBackground: Heterotopic ossification on the enthesis, which develops after subsequent inflammation, is one of the most distinctive features in ankylosing spondylitis (AS). Prostaglandin E2 (PGE-2) serves as a key mediator of inflammation and bone remodeling in AS. Celastrol, a well-known Chinese medicinal herb isolated from Tripterygium wilfordii, is widely used in treating inflammatory diseases, including AS. It has been proven that it can inhibit lipopolysaccharide-induced expression of various inflammation mediators, such as PGE-2. However, the mechanism by which celastrol inhibits inflammation-induced bone forming in AS is unclear.Objective: To investigate whether celastrol could inhibit isolated AS fibroblast osteogenesis induced by PGE-2.Methods: Hip synovial tissues were obtained from six AS patients undergoing total hip replacement in our hospital. Fibroblasts were isolated, primarily cultured, and then treated with PGE-2 for osteogenic induction. Different doses of celastrol and indometacin were added to observe their effects on osteogenic differentiation. Cell proliferation, osteogenic markers, alizarin red staining as well as the activity of alkaline phosphatase were examined in our study.Results: Celastrol significantly inhibits cell proliferation of isolated AS fibroblasts and in vitro osteogenic differentiation compared with control groups in a time- and dose-dependent manner.Conclusion: Our results demonstrated that celastrol could inhibit isolated AS fibroblast proliferation and in vitro osteogenic differentiation. The interaction of PI3K/AKT signaling and Wnt protein may be involved in the process. Further studies should be performed in vivo and animal models to identify the potential effect of celastrol on the bone metabolism of AS patients. Keywords: ankylosing spondylitis, celastrol, osteogenesis, fibroblasts, proliferation, prostaglandin E2